Phenotypic variations between non-transgenic and transgenic maize hybrids - Laserna, María Paula (2012)
The use of transgenic maize (Zea mays, L.) hybrids (Bt, RR, Bt-RR) has simplified crop husbandry, mainly due to a more effective control of pests and weeds. The effects of transgenes insertion on phenotypic traits of maize hybrids are not fully documented, especially without the incidence of pests and weeds. The objectives of this work were to (i) establish phenotypic differences in terms of phenology, growth and yield among single cross conventional maize hybrids and their transgenic versions (Bt, RR and Bt-RR) and (ii) analyze the impact of light stress on inter-plant variability of the different traits under study. Field experiments were conducted in Buenos Aires (34º 36´ S, 58º 26´ W), Argentina during 2008-2009 (Exp 1), 2009-2010 (Exp 2) and 2010-2011 (Exp 3). Genotypes were cultivated at contrasting plant densities (6 and 12 pl m-2 in Exp1 and Exp2, and with 4 inter-plant spaces within the row in Exp3), irrigated, without nutrient limitations, and with chemical and mechanical controls of weed and animal pests. Phenotypic variability of several traits between groups of hybrids and between versions within each group was recorded. Some of these differences were independent of plant density and/or the environment of each experiment while others were detected only under some conditions. For example, the RR versions of both group of hybrids, had the shortest thermal times to anthesis and silking. At high density, DK747MGRR and DK190RR exhibited the largest plant growth rates (PGRCP), the highest inter-plant variability of this trait and the highest ear growth rates during the critical period (EGRCP) for kernel set. However, both genotypes had a low reproductive efficiency (i.e. kernel number per unit of EGRCP), that counterbalanced the high EGRCP. Consequently, the different versions of each group of hybrids had a similar kernel number per plant. We conclude that the introduction of transgenes may alter in some way, the behaviour of plants in different eco-physiological aspects in the absence of pests and weeds.